Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).